The modified NCEP ATP III criteria maybe better than the IDF criteria in diagnosing Metabolic Syndrome among Malays in Kuala Lumpur - Bulgiba Awang; Moy Foong Ming (BMC, 2010)
Abstract Background Metabolic Syndrome is associated with increased risk for type 2 diabetes and cardiovascular diseases. However, different diagnostic criteria have been recommended by different expert groups. In Malaysia, there is a lack of research comparing these different diagnostic criteria. Therefore, it is our aim to study the concordance between the IDF and the modified NCEP ATP III definitions of Metabolic Syndrome among a Malay cohort in Kuala Lumpur; and to demonstrate if all participants have the same cardiometabolic risks. Methods This was an analytical cross sectional study. Ethics approval was obtained and informed consent was given by all participants. Anthropometric measurements, blood pressure, fasting blood glucose and lipid profile were taken following standard protocols. Results Metabolic Syndrome was diagnosed in 41.4% and 38.2% participants using the modified NCEP and IDF criteria respectively. Among those diagnosed with Metabolic Syndrome by modified NCEP, 7.6% were missed by the IDF criteria. Participants diagnosed by the modified NCEP criteria had lower BMI and waist circumference but had higher cardiometabolic risks than those diagnosed with both criteria. Their blood pressure, glucose, total cholesterol and triglyceride were more adverse than the IDF group. This demonstrated that central obesity may not be a prerequisite for the development of increased cardiometabolic risks within this Malay cohort. Conclusion Metabolic syndrome is common in this Malay cohort regardless of the criterion used. The modified NCEP ATP III criteria may be more suitable in diagnosis of metabolic syndrome for this Malay cohort.